Analisis Unsur Ekstrinsik Pada Cerpen “Kado Istimewa” Karya Jujur Prananto - Lela Nurlaela; Muhammad Wisnu Nugraha (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
The purpose of this study is to determine the extrinsic elements of the short story entitled “Kado istimewa” karya Jujur Prananto. Short stories or often called short stories are material from the course of appreciation and study of prose. The method used is a qualitative descriptive method in the form of words. The data obtained in this study are in the form of extrinsic elements sourced from the short story by Dinda Yuni Sari. The results of the analysis are based on the background of society, the background of the author, and the values ​​contained in the short story.